Testing the influence of SDES instructional media on the results of cryptography learning - Soeprijanto Soeprijanto; Aodah Diamah; Prasetyo Wibowo Yunanto (REID (Research and Evaluation in Education), 2020)
This study aims to examine the influence of Simplified Data Encryption System (SDES) simulation on student learning outcomes in Cryptography lessons. The research employed a quasi-experiment. Data analysis to test the SDES simulation model was performed using ANOVA 2x2. The U-Mann Whitney Test was chosen to examine differences in student learning outcomes of treatment groups and control groups, while the effectiveness of the media is determined by differences in student learning outcomes between the pre-test and post-test results in the two groups. The test results show that: (1) There is a difference between the treatment group and control group, indicated by the U-Mann Whitney Test result (Ucount = 15 Utable = 23; α = 0.05), which means there is a difference of student learning outcome between students given learning by DES simulation media and those by PowerPoints Media. (2) There is a difference in the cryptography learning outcomes for the students with the high initial ability between the treatment group and the control group. The test result is Ucount = 0.5 Utable = 2; at α = 0.05. (3) There is no difference in student learning outcomes for low initial ability student groups using the DES simulation media, with high ability students group using PowerPoints Media; the statistical test results show Ucount = 11 Utable = 2; at α = 0.05. This study concludes that using U-Mann Whitney, it can prove that the SDES simulation model developed is effective for improving student learning outcomes in Cryptography lessons.